ANALISIS PENERAPAN PENCATATAN KEUANGAN SEDERHANA PADA UMKM: STUDI KASUS WARMART - Nadhira Khansya Habibah; Dicki Kusmayadi (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
There is a problem where 77,5% of MSMEs lack accurate and adequate financial recording, which hinders effective business management and strategic decision-making. This study aims to analyze the financial recording system of the retail grocery MSME Warmart using the Theory of Planned Behavior (TPB) and Resource-Based View (RBV) approaches. TPB is used to understand the influence of the owner’s attitude, subjective norms, and behavioral control on financial recording practices. At the same time, RBV assesses financial recording as a strategic resource to enhance competitive advantage and business sustainability. The research employs a qualitative method with a single case study approach. Date were collected through direct observation, interviews with the owner and employees of Warmart, and documentation of financial records. The results reveal that financial recording at Warmart is still done manually and limited to recording income and expenses without complete financial reports, such as profit and loss statements and balance sheets. The main obstacles include the owner’s limited understanding of comprehensive recording and operational technology constraints. This study recommends systematic and structured training and mentoring on financial recording for MSMEs to improve financial management accuracy, consistency, and quality. This can support better decision-making and strengthen business competitiveness.